2022
DOI: 10.2337/db22-0294
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-Specific Expression of CIDEC Improves High-Fat Diet–Induced Vascular and Metabolic Dysfunction

Abstract: Cell death-inducing DNA fragmentation factor-α-like effector C (CIDEC), originally identified to be a lipid-droplet associated protein in adipocytes, positively associates with insulin sensitivity. Recently, we discovered that it is expressed abundantly in human endothelial cells (ECs) and regulates vascular function. The present study was designed to characterize the physiological effects and molecular actions of endothelial CIDEC in the control of vascular phenotype and whole-body glucose homeostasis. To ach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…On the other hand, insulin resistance can induce an imbalance in lipoproteins profle alterations that contributes to the development of dyslipidemia and the lipid triad ( 41 ). The abnormal association between insulin resistance and endothelial signal conduction disorder leads to inflammation, which further disrupts the balance between endothelial vasodilator and vasoconstrictor mechanisms, and leads to the formation of atherosclerotic plaque ( 40 , 42 ). New therapies focused on decreasing insulin resistance may be investigated as a potential future therapeutic target for mitigating both CVD and atherosclerotic plaque generation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, insulin resistance can induce an imbalance in lipoproteins profle alterations that contributes to the development of dyslipidemia and the lipid triad ( 41 ). The abnormal association between insulin resistance and endothelial signal conduction disorder leads to inflammation, which further disrupts the balance between endothelial vasodilator and vasoconstrictor mechanisms, and leads to the formation of atherosclerotic plaque ( 40 , 42 ). New therapies focused on decreasing insulin resistance may be investigated as a potential future therapeutic target for mitigating both CVD and atherosclerotic plaque generation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an emerging role for CIDEC as modulator of vascular function and VEGF signaling has been recently proposed [ 49 , 50 ]. Although in our study, CIDEC mRNA was below detection limit in human retina, RPE and choroid, CIDEC expression in vascular endothelial cells has been observed in other human tissue such as subcutaneous or visceral fat [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although in our study, CIDEC mRNA was below detection limit in human retina, RPE and choroid, CIDEC expression in vascular endothelial cells has been observed in other human tissue such as subcutaneous or visceral fat [ 49 ]. Using a mouse expressing human CIDEC in vascular endothelial cells, it was shown that CIDEC enhance vascular remodeling, angiogenesis and stabilize VEGF signaling [ 50 ]. Since the CIDEC rare variants were identified in neovascular AMD patients, it is unlikely that they critically affect this potential pro-angiogenic role of CIDEC.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the ADRB2/PKA signaling pathway promotes lipid synthesis in human lid gland epithelial cells and also provides a potential mechanism and therapeutic target for dry eye disease [ 37 ]. Previous reports have indicated that cell-death-inducing DNA fragmentation factor-α-like effector C ( CIDEC ) is positively relates to insulin sensitivity, whereas the expression of endothelial-specific CIDEC improves vascular and metabolic dysfunction induced by a high-fat diet [ 38 ]. Bi-allelic SLC4A2 loss-of-function mutations in mice and cattle lead to osteopetrosis with osteoclast deficiency [ 39 ].…”
Section: Discussionmentioning
confidence: 99%